The Importance of Ethical Leadership and Employee Performance in Modern Organizations - ETINAGBEDIA, Goodluck; Chuks OKOLIE, Ugo (Pinisi Business Administration Review, 2024)
A leader's transparency, dependability, and uniformity in upholding moral principles are considered aspects of their integrity. Divergent opinions have been expressed regarding what behaviours are ethical modern organizations. This study therefore examined the importance of ethical leadership and employee performance in modern organizations. This paper relies on secondary data and utilizes the content analysis for interpretation of collected data. This paper concludes that clear ethics codes and appropriate policies must be in place to guarantee that all employees know what is expected of them in order to cultivate ethical professionals. Organizations must also show ethical leadership in the recruiting, training, and development processes; additionally, they must recognize and honour employees who uphold ethical standards.